Energy Storage and Transportation Based on Solar Irradiation‐Aided CaO‐Looping. Issue 1 (27th November 2015) - Obermeier, Jonas; Müller, Benjamin; Müller, Karsten; Arlt, Wolfgang
Abstract: For the utilization of surplus solar energy from desert regions in central Europe, a concept for trans‐regional energy storage and transportation based on the reversible chemical reaction of CaO/CaCO3 has been proposed previously. In this context it is necessary to consider potential side reactions and the influences of heat recovery and conversion on efficiency of the thermochemical storage. To realize a zero emission energy distribution cycle, different CO2 ‐recycling strategies are evaluated. The synthetic natural gas (SNG) synthesis is identified as the most suitable technology and a combined CaO/CaCO3 –SNG cycle is developed. Based on process simulation, an overall solar‐to‐electricity efficiency of 9.8 % and an exergetic efficiency of 10.5 % are obtained. The solar hydrogen generation is identified as the most critical step for the overall efficiency. The suggested concept can be competitive to trans‐regional solar energy distribution proposals with parabolic trough power plants and high‐voltage direct‐current (HVDC) lines. Abstract : Closed CO2 and CaCO3 /CaO cycle: A combined synthetic natural gas (SNG) synthesis and CaO/CaCO3 cycle for the storage and transportation of surplus solar energy is introduced and evaluated with respect to the energetic and exergetic efficiencies. The results show that the suggested concept is competitive with alternative trans‐regional solar energy distribution proposals using parabolic trough power plants and high‐voltage direct‐current lines (e.g., DESERTEC).